COMMUNICATIVE CONNOTATION OF PEPSI COLA ADS - Shaheed Salim, Ja’afar (ALBAHITH ALALAMI, 2022)
A trademark is one of the most valuable elements in advertising. At the same time, it is a guarantee for both the producer and the consumer. It prevents the mixing of products with a certain mark with similar products bearing another mark; and creates confidence in the goods of the product. With the increase in the types of goods and products and the emergence of similar goods, producers have turned to the use of the brand to identify their products and seek perfection in manufacture to maintain quality and continuous improvement which ensures good reputation and fame. Hence, commercials for goods and services focused on the brand because they give in-depth connotations with the recipients of these ads. The brand contains words, pictures, letters, or drawings, all of which mean certain things and symbols that address the recipient and pull him/ her towards the advertisement. This will be evident in our approach to the Pepsi Cola ads in one of the satellite channels and the highlight of this sign of communicative connotations expressed by linguistic symbols, verbal and non-verbal.